The Effect of Indirect Compensation on Employee Performance (Case Study at The Khayangan Dreams Villas, Bali, Indonesia) - Ni Made Suastini; Ni Putu Sinthia Damayanthi (Politeknik Pariwisata Bali, 2022)
This study was conducted to identify the effect of indirect compensation on employee performance at The Khayangan Dreams Villas Bali. The research data were collected through questionnaires, interviews, and documentation studies. The research population was the whole 36 employees of The Khayangan Dreams Villas Bali. The amount of the samples was determined with saturated sampling for the sampling method. The data were analyzed using the validity test, reliability test, simple linear regression, t-test, and determination coefficient test assisted by the SPSS 23 version program for Windows. According to the findings, the paid vacation program received the lowest score in the indirect compensation criteria, and the ability in employee performance received the lowest score. To improve these features, it is advised that an evaluation of the paid vacation program be conducted, as well as the creation of employee performance indicators for Khayangan Villas’ personal use.